Effect of Ionizing Radiation on the Bacterial and Fungal Endophytes of the Halophytic Plant Kalidium schrenkianum - Jing Zhu; Xiang Sun; Zhi-Dong Zhang; Qi-Yong Tang; Mei-Ying Gu; Li-Juan Zhang; Min Hou; Amir Sharon; Hong-Li Yuan (Microorganisms, 2021)
Endophytic bacteria and fungi colonize plants that grow in various types of terrestrial and aquatic ecosystems. Our study investigates the communities of endophytic bacteria and fungi of halophyte Kalidium schrenkianum growing in stressed habitats with ionizing radiation. The geochemical factors and radiation (at low, medium, high level and control) both affected the structure of endophytic communities. The bacterial class Actinobacteria and the fungal class Dothideomycetes predominated the endophytic communities of K. schrenkianum. Aerial tissues of K. schrenkianum had higher fungal diversity, while roots had higher bacterial diversity. Radiation had no significant effect on the abundance of bacterial classes. Soil pH, total nitrogen, and organic matter showed significant effects on the diversity of root endophytes. Radiation affected bacterial and fungal community structure in roots but not in aerial tissues, and had a strong effect on fungal co-occurrence networks. Overall, the genetic diversity of both endophytic bacteria and fungi was higher in radioactive environments, however negative correlations were found between endophytic bacteria and fungi in the plant. The genetic diversity of both endophytic bacteria and fungi was higher in radioactive environments. Our findings suggest that radiation affects root endophytes, and that the endophytes associated with aerial tissues and roots of K. schrenkianum follow different mechanisms for community assembly and different paradigms in stress response.